PEMBERDAYAAN KELOMPOK TANI DI DESA WATUAGUNG MELALUI PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH TEMPE - Siti Maro'ah; Findha Annisa Amalia; Jihan Fadhilasari; Muhhammad Jabbaar Ramadhan (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This research addresses the problem of soybean waste from tempeh production and proposes a solution by processing the waste into liquid organic fertilizer (LOF) for plants. This initiative arose from the abundance of liquid tempeh waste in the community of Watuagung Village, Baturetno District, Wonogiri, which poses a risk of environmental problems. This activity aims to empower communities through the utilization of local household industrial waste. By turning this waste into a valuable resource, this service not only offers a sustainable waste management strategy but also increases agricultural productivity. The process involves collecting, processing, and fermenting tempeh waste to produce a liquid fertilizer that is rich in nutrients and suitable for various types of plants. This liquid organic fertilizer (LOF) from tempeh waste will later provide findings showing that the application of this fertilizer significantly improves plant growth and soil health, proving its effectiveness and potential as an environmentally friendly agricultural input. The implementation method of this program is divided into two stages, namely the socialization stage and the demonstration stage. This project highlights the role of community service and student involvement in practical environmental solutions